SymB and SymC, two membrane associated proteins, are required for Epichloë festucae hyphal cell–cell fusion and maintenance of a mutualistic interaction with Lolium perenne. Issue 4 (14th December 2016) - Green, Kimberly A.; Becker, Yvonne; Tanaka, Aiko; Takemoto, Daigo; Fitzsimons, Helen L.; Seiler, Stephan; Lalucque, Hervé; Silar, Philippe; Scott, Barry
Summary: Cell–cell fusion in fungi is required for colony formation, nutrient transfer and signal transduction. Disruption of genes required for hyphal fusion in Epichloë festucae, a mutualistic symbiont of Lolium grasses, severely disrupts the host interaction phenotype. They examined whether symB and symC, the E. festucae homologs of Podospora anserina self‐signaling genes IDC2 and IDC3, are required for E. festucae hyphal fusion and host symbiosis. Deletion mutants of these genes were defective in hyphal cell fusion, formed intra‐hyphal hyphae, and had enhanced conidiation. SymB‐GFP and SymC‐mRFP1 localize to plasma membrane, septa and points of hyphal cell fusion. Plants infected with Δ symB and Δ symC strains were severely stunted. Hyphae of the mutants colonized vascular bundles, were more abundant than wild type in the intercellular spaces and formed intra‐hyphal hyphae. Although these phenotypes are identical to those previously observed for cell wall integrity MAP kinase mutants no difference was observed in the basal level of MpkA phosphorylation or its cellular localization in the mutant backgrounds. Both genes contain binding sites for the transcription factor ProA. Collectively these results show that SymB and SymC are key components of a conserved signaling network for E. festucae to maintain a mutualistic symbiotic interaction within L. perenne . Abstract : The Epichloë festucae transcription factor ProA binds to a conserved motif present in the promoters of symB and symC to activate expression of these genes. SymB and SymC localize to the plasma membrane, septa and points of hyphal fusion. Genetic analysis shows that SymB and SymC are essential for cell‐cell fusion and establishment of a hyphal network in planta to maintain a mutualistic symbiotic interaction with the grass host Lolium perenne